1999
DOI: 10.1046/j.1365-2826.1999.00356.x
|View full text |Cite
|
Sign up to set email alerts
|

Radioligand Assays for Oestradiol and Progesterone Conjugated to Protein Reveal Evidence for a Common Membrane Binding Site in the Medial Preoptic Area‐Anterior Hypothalamus and Differential Modulation by Cholera Toxin and GTPγS

Abstract: In this study membrane oestradiol (E) binding sites in the medial preoptic area-anterior hypothalamus (MPOA-AH) of ovariectomized (OVX) rats were characterized using standard radioligand binding techniques employing E conjugated to bovine serum albumin (BSA) at position 6 and radiolabeled with 125I (E-6-[125I-BSA]). In previous studies binding of a radioactive conjugate of progesterone (P) and BSA (P-3-[125I-BSA]) was examined using the same membrane preparation. E-6-[125I-BSA] binding was linear across a tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…4B). These results, summarized in Table 1, strongly suggest the involvement of G proteins in signal transduction via membrane‐bound progesterone receptors in the fungus and are in accordance with observations by Caldwell et al[10] who, using GTPγS and toxins, demonstrated that G proteins were associated with progesterone and estradiol membrane binding sites in the medial preoptic area–anterior hypothalamus of rat.…”
Section: Resultssupporting
confidence: 91%
“…4B). These results, summarized in Table 1, strongly suggest the involvement of G proteins in signal transduction via membrane‐bound progesterone receptors in the fungus and are in accordance with observations by Caldwell et al[10] who, using GTPγS and toxins, demonstrated that G proteins were associated with progesterone and estradiol membrane binding sites in the medial preoptic area–anterior hypothalamus of rat.…”
Section: Resultssupporting
confidence: 91%
“…SHBG (human SHBG; Lot # 596402 with a ratio of total protein to SHBG of 1.43, giving a purity of ∼70%; Cortex Biochem Inc., San Leandro, Calif., USA) was iodinated by the chloramine T method previously described for conjugated steroids in Caldwell et al [42]. Briefly, 50 µl of 1 mg/ml SHBG in 40 m M Trizma was added to 25 µl chloramine T (0.8 mg/ml) in the vial of Na- 125 I (1 mCi from ICN Pharmaceuticals, Costa Mesa, Calif., USA) for 12 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The MH was dissected out of the MH section by making a rectangular cut with its lateral sides made by vertical sagittal cuts from the medial extent of the optic tracts and with its dorsal edge 1 mm dorsal to the dorsal extent of the third ventricle. These are the same dissections that we have previously used to isolate the MPOA-AH and MH [30, 42, 43, 45, 46]. …”
Section: Methodsmentioning
confidence: 99%